Analysis of Fracture Mechanics of Glued Laminated Lumber Composed of China’s Plantation Wood - Zhang, Zhong-Feng; Huang, Kai; Ye, Yong-Jun; Shi, Jun-You; Zhang, Xu (Asian Journal of Chemistry, 2014)
Increasingly, glued laminated wood, commonly referred to as Glulam, is being produced from Chinese plantation wood, the fracture behaviour of which is the key factor for meeting the requirements for being used as engineered wood for bridges. Both whole factor test methods and nonlinear finite element analyses were used to analyze the fracture mechanics of Chinese Glulam. Test results showed that the fracture modes were initially sliding breaks and then tearing under vertical loads and open fractures under parallel loads. The fracture modes had no correlation to the reinforcing materials under parallel loading and it was realistic for glued laminated lumber to support weight under vertical loading. The simulation results of the nonlinear finite elemental analysis showed that the aluminum foil and glass fiber cloth used in Glulam had an obvious reinforcing effect and both the thickness and length had an interactive effect on the ultimate bearing capacity. It was also seen that the simulation results were consistent with the test results.